High Prevalence of Biofilm-Forming MRSA in the Conjunctival Flora in Chronic Dacryocystitis. (17th February 2019) - Mitra, Sanchita; Chayani, Nirupama; Mohapatra, Dharitri; Barik, Manas Ranjan; Sharma, Savitri; Basu, Soumyava
ABSTRACT: Objectives : To report the microbiological spectrum of conjunctival flora and prevalence of biofilm-forming Methicillin-resistant Staphylococcus aureus (MRSA) in conjunctival flora in chronic dacryocystitis. Design : Prospective, case-control study. Methods : We included patients with unilateral chronic dacryocystitis, and their unaffected eyes as control. Microbiological profile and antibiotic susceptibility of the isolates was determined by standard microbiological procedures. S. aureus isolates were further evaluated for Methicillin resistance by Oxacillin resistance screening agar method and mec A polymerase chain reaction (PCR) and for biofilm synthesis by Congo red agar method, Microtitre plate (MTP) assay, and ica A and ica D PCR. Results : We found 95 patients with unilateral chronic dacryocystitis. Aerobic Gram-positive isolates (74.2%, n = 72) were more than Gram-negative (25.7%, n = 25) or anaerobic isolates (20.5%, n = 25). S. aureus was most common (46.4%, n = 45), followed by Pseudomonas aeruginosa (10.3%, n = 10). Gram-positive isolates showed highest sensitivity to Linezolid (100%) and higher generation fluoroquinolones. Gram-negative isolates showed good sensitivity (>90%) to all tested antibiotics. S. aureus isolates showed MRSA prevalence as 93.5% and 96.9% by Oxacillin resistance screening agar method and mec A PCR, respectively. Biofilm formation was found in 71.8% MRSA isolates by MTP assay and 58.1% MRSA isolates were resistant to ≥3 classes of antibiotics. Conclusions : Gram-positive organisms, specifically S. aureus, are the major etiological agent in chronic dacryocystitis. There is high prevalence of MRSA in these isolates and concurrent biofilm formation.